Fuzzy small right ideals of rings - P. Dheena; G. Mohanraj (Journal of Hyperstructures)
We introduce the notion of fuzzy small right ideal,fuzzy small right prime ideal and fuzzy maximal small right ideal in a ring. We have obtained necessary and sufficient condition for a fuzzy small right ideal to be fuzzy small prime right ideal. We have also shown that fuzzy Jacobson radical is the sum of fuzzy small right ideals.